Effect of feeding mango (Mangifera indica) seed kernel on the performance of broilers - Kumar, P Vasantha; Ravi, R; Mohan, B; Purushothaman, M R (The Indian Journal of Animal Sciences, 2011)
To find out the performance of broilers fed graded levels of mango seed kernel (MSK), chicks (270 numbers) were assigned to 6 treatment groups having 45 birds in each group in 3 replicates and fed diets (isocaloric and isonitrogenoLls) containing MSK @O, 5,10,15,20 and 25% levels replacing maize from 0 to 6 weeks of age. Weight gain was similar to control when MSK was used in the diet at 5% in starter phase (0-3 weeks) or LIp to 20% in finisher phase (4-6 weeks) or 10% in both phases. The feed intake was not affected by dietary treatments during different phases of growth. In comparison to control, the feed efficiency was significantly poor in all the MSK fed groups at starter phase whereas it was similar in 15 and 10% MSK fcd groups at finisher phase and both phases, respectively. The feed cost/kg of weight gain increased linearly with each level of MSK increase in the diet. The blood parameters, carcass characteristics and organoleptic evaluation of meat did not show any significant variation between groups. It can be concluded that MSK can be included in the diet of broilers up to 10% during 0-6 weeks of age or up to 15% during 4-6 weeks of age.